Penguatan Literasi Akhlak Santri di Era Digital: Perspektif Kitab Ihya’ Ulumuddin dalam Pendidikan Pesantren - Wanto, Wanto (Annusfy : Journal of Multidisciplinary Research, 2025)
This study aims to examine the concept of moral literacy in Al-Ghazali’s Ihya’ Ulumuddin and its relevance to the moral development of pesantren students in the digital era. The research employs a library study with a qualitative approach through content analysis of classical texts combined with contemporary theories of moral education, psychology, and sociology. The findings reveal that moral literacy in Al-Ghazali’s perspective is not limited to normative understanding, but rather an integration of knowledge, practice, and inner refinement through tazkiyatun nafs, muraqabah, muhasabah, and mujahadah. Pesantren provide a conducive ecology for moral internalization through the exemplarity of the kiai, daily habituation of adab, and learning communities. The discussion highlights key digital-era challenges, including moral degradation, attention distraction, identity fragmentation, and moral disengagement. Integrating the values of Ihya’ Ulumuddin with modern educational strategies such as role modeling, authentic assessment, adaptive moral curriculum, and digital ecology management can strengthen students’ moral literacy. In conclusion, Ihya’ Ulumuddin remains highly relevant as a multidisciplinary framework for formulating resilient moral education strategies in the face of digitalization